Immune mediators of pathology in neurobrucellosis: from blood to central nervous system - Rodriguez, Ana María (2019)
Neurobrucellosis, which is the most morbid form of brucellosis disease, presents with inflammatory signs and symptoms. Recent experimental evidence clearly indicates that deregulation of astrocytes and microglia caused by Brucella infection creates a microenvironment in the central nervous system (CNS) in which secretion of pro-inflammatory mediators lead to destabilization of the glial structure, the damage of the blood brain barrier (BBB) and neuronal demise. This review of Brucella interactions with cells of the CNS and the BBB is intended to present recent immunological findings that can explain, at least in part, the basis for the inflammatory pathogenesis of the nervous system that takes place upon Brucella infection.